Próba zdefiniowania projektu w ramach zarządzania projektami - Klinowski, Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Management by projects is more and more often applied by companies nowadays. The author presents different definition of project and gifs his own description of this term. The paper also contains a remark about specific approach to project issue in polish language. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1178, s. 58-62